Frommer's 99 Germany - Porter, Darwin (Macmillan USA, 1999)
This guide provides complete coverage of the country's attractions: tourist figures are on the way up, with Weimar being the 1999 European City of Culture, and the year 2000 seeing Expo 2000 in Hanover and the 10-yearly passion play in Oberammergau. Includes a full-colour fold-out map.